2018
DOI: 10.1097/md.0000000000013652
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin use on survival outcomes in non-small cell lung cancer treated with platinum

Abstract: Preclinical evidence suggests that metformin, a widely used antidiabetic drug, may have a sensitizing effect on platinum. The purpose of this study was to evaluate the survival outcomes for non-small cell lung cancer (NSCLC) patients with type 2 diabetes mellitus (T2DM) using metformin during platinum-based chemotherapy.The clinicopathological parameters and survival data of 75 NSCLC patients with T2DM from January 2008 to December 2011 were collected and analyzed retrospectively. Patients were divided into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The results of some studies showed that metformin, when used in combination with antineoplastic agents, appears to improve the antitumor effect of anticancer agents ( Tan et al, 2011 ; Chen et al, 2015 ; Kong et al, 2015 ; Lin et al, 2015 ; Xu et al, 2015 ; Afzal et al, 2019 ; Arrieta et al, 2019 ; Hung et al, 2019 ). However, several studies have reported no effect of adjuvant metformin therapy on survival outcomes ( Ahmed et al, 2015 ; Sayed et al, 2015 ; Wink et al, 2016 ; Lu et al, 2018 ; Wen-Xiu et al, 2018 ; Li et al, 2019 ). Moreover, no systematic review of previous studies has evaluated the efficacy of metformin in combination with anticancer drugs for the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies showed that metformin, when used in combination with antineoplastic agents, appears to improve the antitumor effect of anticancer agents ( Tan et al, 2011 ; Chen et al, 2015 ; Kong et al, 2015 ; Lin et al, 2015 ; Xu et al, 2015 ; Afzal et al, 2019 ; Arrieta et al, 2019 ; Hung et al, 2019 ). However, several studies have reported no effect of adjuvant metformin therapy on survival outcomes ( Ahmed et al, 2015 ; Sayed et al, 2015 ; Wink et al, 2016 ; Lu et al, 2018 ; Wen-Xiu et al, 2018 ; Li et al, 2019 ). Moreover, no systematic review of previous studies has evaluated the efficacy of metformin in combination with anticancer drugs for the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer is among the most lethal tumors and treatment frequently has a poor prognosis. A recent publication shows that metformin has no impact in platinum-based therapy for NSCLC [ 33 ]. Another publication shows that metformin enhances cisplatin-induced sensitivity to radiotherapy in two wild type P53 cell lines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the remaining reports were included after review of the full texts, and 11 available studies were included from previous relevant meta-analyses. Thus, a total of 19 studies were included in this meta-analysis (Tan et al, 2011;Ahmed et al, 2015;Chen et al, 2015;Lin et al, 2015;Sayed et al, 2015;Wink et al, 2016;Wen-Xiu et al, 2018;Afzal et al, 2019;Arrieta et al, 2019;Hung et al, 2019;Li et al, 2019;Su et al, 2020;Cortellini et al, 2021;Han et al, 2021;Jacobi et al, 2021;Lee et al, 2021;Skinner et al, 2021;Tsakiridis et al, 2021;Wang Y. et al, 2021). The specific literature retrieval process is presented in Figure 1.…”
Section: Literature Search and Retrievalmentioning
confidence: 99%